2004
DOI: 10.1081/sl-120038761
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spectroscopic Representations in Student‐Generated Atomic Models

Abstract: The goal of this paper is to illustrate college students' levels of sophistication of their spectroscopic representations (SRs). For example, a photon is drawn as a wavy line, which might be used to enhance their atomic models (AMs). Study 1 was a quantitative study in which 70 students, enrolled in first semester general chemistry, drew or described their own model of the atom. Despite the fact that they had just completed a unit on atomic structure, only 30.6% of these students were classified as having a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Sanger (2000) used student drawings to show that successful students use better strategies than unsuccessful students when distinguishing elements, compounds, and mixtures in pictorial images. Suits and Hypolite (2004) reported that students can actually develop misconceptions from drawing static representations of dynamic processes, such as electron-photon interactions in atoms. Kelly and Jones (2007) found that students could draw correct representations of the particulate nature of matter after viewing animations of molecular behavior, without actually understanding what their pictures meant.…”
Section: Introductionmentioning
confidence: 99%
“…Sanger (2000) used student drawings to show that successful students use better strategies than unsuccessful students when distinguishing elements, compounds, and mixtures in pictorial images. Suits and Hypolite (2004) reported that students can actually develop misconceptions from drawing static representations of dynamic processes, such as electron-photon interactions in atoms. Kelly and Jones (2007) found that students could draw correct representations of the particulate nature of matter after viewing animations of molecular behavior, without actually understanding what their pictures meant.…”
Section: Introductionmentioning
confidence: 99%